Getting an insider's perspective to better understand women's empowerment - Jackson-deGraffenried, Meredith; Kalam, Md. Abul (CGIAR GENDER Impact Platform, 2022)
In the past, methods for measuring women’s empowerment have often relied on indicators defined by outsiders. In a recent project in Bangladesh, we worked with local communities to gain an insider’s perspective and create a custom scale to better capture what women’s empowerment means for them.